PENGARUH MODEL ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA SISWA KELAS III PADA MATA PELAJARAN BAHASA INDONESIA - Niweroh; Kusuma, Rendra Sakbana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out whether there is an influence on students' speaking skills using the Role Playing Model in class III Indonesian language subjects at UPTD SDN Sepulu 1 with this quantitative research using the research design used is a pre-Experimental Designs design. The sample used by class III students was 26 students in total. The instrument used is a test of students' understanding of learning. Meanwhile, the analysis tests are validity, reliability, normality test, and paired sample t-test with the help of the IBM SPSS application v21.0. This is proven by the use of role playing models on students' speaking skills, obtaining a significant value (2-tailed) of 0.000<0.05, which states that there is an influence on students' speaking skills using role playing models.